How AI is Revolutionizing Drug Discovery: Speed, Precision, and the Future of Medicine - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The process of discovering and developing a new drug is notoriously long, expensive, and fraught with failure. On average, it takes over a decade and costs b...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation